Archontic Aporias: the mediums of memory - Arbuckle, Julia Ruth (Rhodes University, Faculty of Humanities, Department of Fine Art)
Contextualising my research within the Eastern Cape as a descendant of 1820 settlers, I question the modalities of historical recollection by introducing memory as a viable mode of archival production alongside that of the archive. Through interrogating Eastern Cape archival institutes and employing an autoethnographic approach to my familial archives, I show that archival curation affects the gaps, schisms, and interpretations of archives as much as the 'unreliability' of memory. I rely on definitions from Jacques Derrida and literature from Achille Mbembe and Verne Harris, as well as reflexive methodologies, to engage the ways of remembering the past and methods of storytelling. With this undertaking, I expose the aporias within archival processes. This written component is part of broader research that encompasses theoretical study and a practice-based Fine Arts research project culminating in an exhibition that shares themes of memory, archive, trauma, and curatorial and personal heritage management. This research engages in case studies of artworks by Angela Deane and Maureen de Jager to contextualise and position the creative process.
Keywords: Practice research; Eastern Cape (South Africa) History; Autoethnography; Information storage and retrieval systems Memory; Archives -- South Africa -- Eastern Cape; Aporia; Memory in art; Archives in art